Rhomboid intramembrane protease RHBDL4 triggers ER-export and non-canonical secretion of membrane-anchored TGFα - Wunderle, Lina; Knopf, Julia Daniela; Kühnle, Nathalie; Morlé, Aymeric; Geiger, Beate; Adrain, Colin; Strisovsky, Kvido; Freeman, Matthew; Lemberg, Marius (Scientific reports, 2016)
Rhomboid intramembrane proteases are the enzymes that release active epidermal growth factor receptor (EGFR) ligands in Drosophila and C. elegans, but little is known about their functions in mammals. Here we show that the mammalian rhomboid protease RHBDL4 (also known as Rhbdd1) promotes trafficking of several membrane proteins, including the EGFR ligand TGFα, from the endoplasmic reticulum (ER) to the Golgi apparatus, thereby triggering their secretion by extracellular microvesicles. Our data also demonstrate that RHBDL4-dependent trafficking control is regulated by G-protein coupled receptors, suggesting a role for this rhomboid protease in pathological conditions, including EGFR signaling. We propose that RHBDL4 reorganizes trafficking events within the early secretory pathway in response to GPCR signaling. Our work identifies RHBDL4 as a rheostat that tunes secretion dynamics and abundance of specific membrane protein cargoes.